2011
DOI: 10.1161/circulationaha.110.006304
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Clinical Features, and Outcomes of Thrombosis Associated With Pediatric Cardiac Surgery

Abstract: Background— Thrombosis, usually considered a serious but rare complication of pediatric cardiac surgery, has not been a major clinical and/or research focus in the past. Methods and Results— We noted 444 thrombi (66% occlusive, 60% symptomatic) in 171 of 1542 surgeries (11%). Factors associated with increased odds of thrombosis were age <31 days (odds ratio [OR], 2.0; P =0.002), baseline oxygen saturation &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 43 publications
5
124
0
6
Order By: Relevance
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study of children undergoing surgery for congenital heart disease, clinically-evident thrombosis was noted in 11%, 53 whereas in single ventricle patients before Fontan, 25% to 40% of patients had clinically-evident thrombosis. 3 In both scenarios, clinically-evident thrombosis was associated with increased morbidity and mortality.…”
Section: Interventional Studies -Acute Treatment Of Thrombotic Complimentioning
confidence: 98%
“…The identification of certain high-risk cardiac surgery subgroups that are expected to have a prolonged recovery 53 would provide a promising study scenario. Another scenario for clinical trials is the prevention and management of venous and arterial thrombosis related to vascular access associated with infant cardiac catheterization.…”
Section: Interventional Studies -Thromboprophylaxis In Prevalent Popumentioning
confidence: 99%
See 1 more Smart Citation
“…The highest mortality period remains the first year post-transplant, most often a result of rejection or infection. It is recognized that clinically significant thrombosis occurs with increased frequency in patients wait-listed for heart transplant; however, the incidence of post-transplant thrombosis has not been well defined [31,32]. In a single-center study, Law et al [31] found a thrombosis prevalence of 12.2% in pediatric patients awaiting heart transplantation despite universal antithrombotic therapy in this population (various individualized regimens).…”
Section: Epidemiologymentioning
confidence: 99%